Performance study of a 3×1×1 m3 dual phase liquid Argon Time Projection Chamber exposed to cosmic rays. (26th August 2021) - Aimard, B.; Aizawa, L.; Alt, C.; Asaadi, J.; Auger, M.; Aushev, V.; Autiero, D.; Balaceanu, A.; Balik, G.; Balleyguier, L.; Bechetoille, E.; Belver, D.; et al.
Abstract: We report the results of the analyses of the cosmic ray data collected with a 4 tonne (3×1×1 m 3 ) active mass (volume) Liquid Argon Time-Projection Chamber (TPC) operated in a dual-phase mode. We present a detailed study of the TPC's response, its main detector parameters and performance. The results are important for the understanding and further developments of the dual-phase technology, thanks to the verification of key aspects, such as the extraction of electrons from liquid to gas and their amplification through the entire one square metre readout plain, gain stability, purity and charge sharing between readout views.